Climate change and the macro-economy: a critical review - Batten, Sandra (London, 2018)
"Climatic factors can directly affect economic outcomes such as output, investment and productivity, and understanding the economic consequences of climate change is becoming a necessity not just for climate economists but also for a wider range of economic professionals involved in modelling and forecasting macroeconomic variables. The focus of this review is on the key theoretical and empirical modelling issues in the analysis of the macroeconomic risks deriving from climate change. The paper develops the taxonomy introduced by a number of previous Bank of England studies, which distinguish between physical and transition risks of climate change. The paper then identifies the different channels through which these risks are transmitted to the macro-economy, either through (unpredictable) economic shocks or through predictable, longer-term impacts. The different approaches to modelling these macroeconomic effects are then discussed and assessed in light of the increasing need to routinely monitor and quantify the impact of emerging climate change risks on the economy."